Полные интегро-дифференциальные уравнения Вольтерра второго порядка, неразрешенные относительно старшей производной - Копачевский, Н.Д.; Сёмкина, Е.В. (Український математичний журнал, 2014)
Доведено теореми про розв'язність задач Коші для повних лінійних інтегро-диференціальних рівнянь Вольтерра другого порядку у гільбертовому просторі. Для повного рівняння залежно від підпорядкованості операторних коефіцієнтів розглянуто три основних класи рівнянь. We prove the theorem on solvability of the Cauchy problem for the complete Volterra integrodifferential linear equations of the second order in a Hilbert space. For a complete equation, we consider three main classes of equations depending on the ordering of operator coefficients.